A Compendium of Formulae for Natural Frequencies of Offshore Wind Turbine Structures - Ramon Varghese (Energies, 2022)
The design of an offshore wind turbine system varies with the turbine capacity, water depth, and environmental loads. The natural frequency of the structure, considering foundation flexibility, forms an important factor in structural design, lifetime performance estimates, and cost estimates. Although nonlinear numerical analysis in the time domain is widely used in the offshore industry for detailed design, it becomes necessary for project planners to estimate the natural frequency at an earlier stage and rapidly within reasonable accuracy. This paper presents a compendium of mathematical expressions to compute the natural frequencies of offshore wind turbine (OWT) structures on various foundation types by assimilating analytical solutions for each type of OWT, obtained by a range of authors over the past decade. The calculations presented can be easily made using spreadsheets. Example calculations are also presented where the compiled solutions are compared against publicly available sources.